Innovative work behavior and personality traits: Examining the moderating effects of organizational tenure. Issue 1 (20th November 2017) - Woods, Stephen A.; Mustafa, Michael James; Anderson, Neil; Sayer, Benjamin
Abstract : Purpose: The literature on individual differences in innovative work behavior (IWB) reveals inconsistencies in the relations of personality traits and tenure on innovation at work. To provide greater clarity about the effects of these antecedents, the purpose of this paper is to report a study of the moderating effects of tenure on the associations of traits and IWB, and apply a theoretical lens based on the trait-activation theory. Design/methodology/approach: In all, 146 employees of a UK-based financial institution completed measures of conscientiousness and openness, and had three aspects of IWB (idea generation, promotion, and realization) rated by their line-supervisor. All participants were on graduate training programs. Hierarchical regression analyses were used to test the moderating effects of tenure on the associations of the self-reported traits with the supervisor-rated IWB outcomes. Findings: Tenure moderated the effects of conscientiousness on IWB, with highly conscientious employees being less innovative with longer tenure. Tenure moderated the effect of openness with idea generation with highly open employees generating more ideas if they were longer tenured. Practical implications: Management of innovation requires differentiated strategies based on the personality traits and tenure of individual employees. Implications for recruitment, socialization and development are discussed. Originality/value: This is the first study to examine empirically the interactions of traits and contextual factors (i.e. organizational tenure) on IWB, framed around a strong theoretical foundation (i.e. trait activation theory). The study also makes notable contributions by measuring innovative behavior using a supervisor-rated and multidimensional approach.